2021
DOI: 10.3390/ma14102631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed Recycled Aggregate on the Mechanical Strength and Microstructure of Concrete under Different Water Cement Ratios

Abstract: Mixed recycled aggregate (MRA) is a kind of recycled aggregate containing discarded bricks and other impurities that is inferior to ordinary recycled concrete aggregate. To study the effect of MRA in concrete, specimens with 100% MRA under different water–cement ratios (W/C) of 0.50, 0.42, 0.36 and 0.30 were prepared, and the mechanical properties and microstructure were tested. Results show that compared with ordinary concrete, the compressive strength of mixed recycled aggregate concrete (MRAC) with the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Several studies [22], [23] and [24] have shown that recycled construction aggregates show higher porosity than natural aggregates and the result from Fig. 15e and 15e' also confirms this.…”
Section: Microstructure Analysissupporting
confidence: 68%
“…Several studies [22], [23] and [24] have shown that recycled construction aggregates show higher porosity than natural aggregates and the result from Fig. 15e and 15e' also confirms this.…”
Section: Microstructure Analysissupporting
confidence: 68%
“…Several studies [22], [23] and [24] have shown that recycled construction aggregates show higher porosity than natural aggregates and the result from Fig. 15e and 15e' also confirms this.…”
Section: Microstructure Analysissupporting
confidence: 62%
“…ported by the literature [20,21]. Moreover, the role of hydrogen peroxide in modulating pore size is noteworthy.…”
Section: Microstructurementioning
confidence: 93%